DEVELOPMENT OF BLENDED LEARNING MODELS TO IMPROVE THE LEARNING EFFECTIVENESS IN HIGHER EDUCATION - Abdul Wahid; Nur Afni Nur Afni; Suarni Suarni (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to: 1) Know the description of needs analysis in blended learning at the Islamic University of Makassar;2) Produce products in the form of model books and blended learning tools that are practical and effective to increase the effectiveness of learning at the Islamic University of Makassar. The subjects of this study were students and lecturers of the Elementary School Teacher Education Study Program (PGSD) of the Faculty of Teacher Training and Education, Islamic University of Makassar. The research and development procedure used is a 4-D (Four-D) model: Define, Design, Develop and Disseminate. The data collection techniques are observation, interviews, tests, questionnaires and documentation. The research instrument uses an instrument to observe the implementation of learning, a test instrument for assessing student learning outcomes, and a validation sheet for learning tools. The data analysis technique is carried out using; 1) analysis of the level of practicality and effectiveness; 2) analysis of student and lecturer response data. This study's results show the need to develop a blended learning model to increase the effectiveness of high-level learning. The practicality and effectiveness test results state that this model has proven to be very practical and effectively used based on the results of observations of learning implementation and questionnaires of lecturer and student responses.